Inhalation gases or gaseous mediators as neuroprotectants for cerebral ischaemia. - Sutherland, B; Harrison, J; Nair, S; Sammut, I (2013)
Ischaemic stroke is one of the leading causes of morbidity and mortality worldwide. While recombinant tissue plasminogen activator can be administered to produce thrombolysis and restore blood flow to the ischaemic brain, therapeutic benefit is only achieved in a fraction of the subset of patients eligible for fibrinolytic intervention. Neuroprotective therapies attempting to restrict the extent of brain injury following cerebral ischaemia have not been successfully translated into the clinic despite overwhelming pre-clinical evidence of neuroprotection. Therefore, an adequate treatment for the majority of acute ischaemic stroke patients remains elusive. In the stroke literature, the use of therapeutic gases has received relatively little attention. Gases such as hyperbaric and normobaric oxygen, xenon, hydrogen, helium and argon all possess biological effects that have shown to be neuroprotective in pre-clinical models of ischaemic stroke. There are significant advantages to using gases including their relative abundance, low cost and feasibility for administration, all of which make them ideal candidates for a translational therapy for stroke. In addition, modulating cellular gaseous mediators including nitric oxide, carbon monoxide, and hydrogen sulphide may be an attractive option for ischaemic stroke therapy. Inhalation of these gaseous mediators can also produce neuroprotection, but this strategy remains to be confirmed as a viable therapy for ischaemic stroke. This review highlights the neuroprotective potential of therapeutic gas therapy and modulation of gaseous mediators for ischaemic stroke. The therapeutic advantages of gaseous therapy offer new promising directions in breaking the translational barrier for ischaemic stroke.